2020
DOI: 10.1055/a-1240-0027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EUS-guided conventional smear and liquid-based cytology in pancreatic lesions: A systematic review and meta-analysis

Abstract: Background and study aims Endoscopic ultrasound (EUS)-guided fine-needle aspiration (EUS-FNA) has limitations of inadequate sampling and false-negative results for malignancy. It has been performed using conventional smear (CS) cytology with rapid on-site evaluation (ROSE) with reasonable diagnostic accuracy. An alternative to ROSE is liquid-based cytology (LBC). Commonly used LBC techniques include precipitation-based (SurePath™) and filtration-based (ThinPrep®, CellPrep®). Data regarding the diagnostic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…The main reason for false-negative results was that when using conventional smear cytology, only segmental liquid sample was obtained for smear specimens, which might not fully represent all pathological changes, leading to the misdiagnosis of some neoplastic lesions. According to a recent meta-analysis by Saurabh et al .,[ 24 25 ] the overall diagnostic accuracy, sensitivity, and specificity of EUS-guided smear cytology in pancreatic lesions was 79.7%, 79.2%, and 99.4%, which was close to the results of this study, meaning that the diagnostic efficiency of Diff-Quik-stained specimens in this study had reached the average level of smear cytology. Notably, touch imprint cytology (TIC) is a cytological technique often applied in the frozen section of intraoperative pathology to determine whether it is benign or malignant.…”
Section: Discussionsupporting
confidence: 86%
“…The main reason for false-negative results was that when using conventional smear cytology, only segmental liquid sample was obtained for smear specimens, which might not fully represent all pathological changes, leading to the misdiagnosis of some neoplastic lesions. According to a recent meta-analysis by Saurabh et al .,[ 24 25 ] the overall diagnostic accuracy, sensitivity, and specificity of EUS-guided smear cytology in pancreatic lesions was 79.7%, 79.2%, and 99.4%, which was close to the results of this study, meaning that the diagnostic efficiency of Diff-Quik-stained specimens in this study had reached the average level of smear cytology. Notably, touch imprint cytology (TIC) is a cytological technique often applied in the frozen section of intraoperative pathology to determine whether it is benign or malignant.…”
Section: Discussionsupporting
confidence: 86%
“…[10,15] (LeBlanc, ThinPrep 75.5% vs CS 95.7%; de Luna R., ThinPrep 67% vs CS 84%) However, 2 previous studies using ThinPrep LBC and a recent meta-analysis of pancreatic lesions reported that ThinPrep LBC underperformed CSs. [16] In ThinPrep LBC, sample loss occurred during the collection process in up to 38% of the samples, so the diagnostic rate was lower than that of SurePath. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Conducting a cytologic assessment on samples acquired through FNA with a conventional 25‐gauge needle provides higher diagnostic accuracy than a histologic assessment 6,17,18 . Compared to CS cytology without ROSE, the precipitation‐based LBC technique (SurePath; Becton, Dickinson and Company) has attracted attention because of its sensitivity for malignant pancreatic lesions 19 . We performed precipitation‐based LBC for samples acquired through FNA with a conventional 25‐gauge needle to increase the diagnostic accuracy of our technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also proposed that 25G‐FNA needles were superior to 22G‐FNA needles in terms of the overall diagnostic accuracy of cytologic findings 6,17,18 . While cytologic evaluation has traditionally been performed with conventional smear cytology, whereas recent studies have proposed that precipitation‐based and liquid‐based cytology (LBC) (SurePath, Becton, Dickinson and Company, Franklin Lakes, New Jersey, USA) provides superior diagnostic detail in the absence of rapid on‐site evaluation (ROSE) 19 . We compared the diagnostic ability of EUS‐FNB histological examination using 22G‐FNB‐H and EUS‐FNA‐ liquid‐based cytological examination using a conventional 25G‐FNA‐LBC in solid pancreatic lesions.…”
Section: Introductionmentioning
confidence: 99%